2013
DOI: 10.1016/j.ejvs.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Low-density Lipoprotein Receptor-related Protein-1 in Chinese Patients with Abdominal Aortic Aneurysm

Abstract: Our pilot result suggests that a reduction in LRP1 protein expression may be associated with aneurysm progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In humans, LRP1 has been linked to the development of abdominal aortic aneurysms based on genetic associations and changes of LRP1 protein abundance in aneurysm tissue 11-13 . Therefore, it was predicted that SMC deletion of LRP1 would promote development of AAAs in normocholesterolemic mice during AngII infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, LRP1 has been linked to the development of abdominal aortic aneurysms based on genetic associations and changes of LRP1 protein abundance in aneurysm tissue 11-13 . Therefore, it was predicted that SMC deletion of LRP1 would promote development of AAAs in normocholesterolemic mice during AngII infusion.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A role for LRP1 in human AAAs has also been inferred by reduced abundance of LRP1 protein in aneurysmal tissue. 13 In addition to an implied role in AAAs, exome sequencing of LRP1 identified a missense mutation in patients with thoracic aortic aneurysms that are afflicted with Marfan syndrome. 14 These recent studies provide the basis for a potential role of LRP1 within aortic aneurysm formation.…”
Section: Introductionmentioning
confidence: 99%
“…LRP1 is also supposed to promote protective effect against aneurysm formation (reviewed by Strickland et al 2014). It was reported that LRP1 expression is decreased on the tissue of human abdominal aortic aneurysm (Chan et al 2013). The structure and function of the brain microvessels are likely to be different from large arteries including aortas, and the MV did not show obvious vascular abnormal changes in this study.…”
Section: Discussionmentioning
confidence: 73%
“…Low-density lipoprotein receptor-related protein 1 (LRP1) demonstrated significant association with AAA size ( P = 0.0042) [58]. In a small pilot study in 12 patients by Chan et al [59], lipoprotein receptor-related protein 1 (LRP1) expression was found significantly lower in AAA patients than in controls, while no significant correlation was shown between LRP1 expression and the size of AAA ( P > 0.05). These results suggest that a reduction in LRP1 expression could be associated with aneurysm progression.…”
Section: Resultsmentioning
confidence: 99%